أثر ترسيم الأمازيغية في تحقيق الأمن اللغوي في الجزائر: Impact of Amazigh demarcation in achieving linguistic security in Algeria - معزوز عبد الحليم (Maalim, 2021)
. Abstract: Language in society plays a pivotal role beyond the communicative task that has been crammed into it through communicative theory, and the fact that the role of language is much greater, by investing in the right direction it contributes to cultural, social, psychological, and even economic goals. In the case of Algeria, serious efforts have been made in recent years to develop a language policy commensurate with its human composition, in order to maintain cultural balance, establish ways of linguistic unity and achieve linguistic security. This was reflected in Algeria's recent constitutional amendment in promoting Amazigh, which is the original language of Algerians and North Africans in general, as the Constitution made Amazigh an official national language in the country, and called for the establishment of an academy to lay the foundations through which the general foundations of Amazigh are laid, from defining the line in which it is embodied, grammar and other foundations that facilitate the teaching of Amazigh. This article wants to highlight the impact of Amazigh demarcation in embodying linguistic security, achieving national unity in Algeria and promoting a sense of belonging among Algerians.